2023
DOI: 10.5194/hess-27-599-2023
|View full text |Cite
|
Sign up to set email alerts
|

Controls on leaf water hydrogen and oxygen isotopes: a local investigation across seasons and altitude

Abstract: Abstract. The stable oxygen (δ18Oleaf) and hydrogen (δ2Hleaf) isotopes of leaf water act as a bridge that connects the hydroclimate to plant-derived organic matter. However, it remains unclear whether the source water (i.e., twig water, soil water, and precipitation) or meteorological parameters (i.e., temperature, relative humidity, and precipitation) are the dominant controls on δ18Oleaf and δ2Hleaf. Here, we reported a seasonal analysis of δ18Oleaf and δ2Hleaf together with isotopes from potential source wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Hence, variations in the plant wax record presumably reflect a combined effect of upstream depletion, precipitation amount, and atmospheric circulation changes 3,20 , where lower δ 2 H wax values indicate an increased EASM intensity, with more precipitation sourced from the Pacific Ocean, whereas higher δ 2 H wax values indicate less precipitation, derived from more local sources 3,20 . However, δ 2 H wax may also be influenced by vegetation change, as the fractionation of hydrogen isotopes during leaf wax synthesis differs between vegetation types 43 . For example, larger fractionation occurs in grasses than in shrubs 41 , and may thus introduce variations in δ 2 H wax independent of climate.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, variations in the plant wax record presumably reflect a combined effect of upstream depletion, precipitation amount, and atmospheric circulation changes 3,20 , where lower δ 2 H wax values indicate an increased EASM intensity, with more precipitation sourced from the Pacific Ocean, whereas higher δ 2 H wax values indicate less precipitation, derived from more local sources 3,20 . However, δ 2 H wax may also be influenced by vegetation change, as the fractionation of hydrogen isotopes during leaf wax synthesis differs between vegetation types 43 . For example, larger fractionation occurs in grasses than in shrubs 41 , and may thus introduce variations in δ 2 H wax independent of climate.…”
Section: Resultsmentioning
confidence: 99%
“…It is also apparent that the observed seasonal cycle of datm( 18 O) was well reproduced by the simulation that incorporated the dLW( 18 O) represented by the thick dashed blue line in Figure 7c. Some past studies have reported seasonal variations of dLW( 18O) (e.g., Welp et al, 2008;Plavcová et al, 2018;Cernusak et al, 2022;Liu et al, 2023). Welp et al (2008) O).…”
Section: Numerical Simulations Of Dlw( 18 O) Using the 3-d Model Miro...mentioning
confidence: 99%